Silent winter : our chemical world and chronic illness - Malaczynski-Moore, Joanna, 1977- (Algora Publishing, 2021)
""Silent Winter" is about the spread of toxic chemicals in our lives and their role in the growing prevalence cancer, chronic fatigue, diabetes, asthma digestive issues, depression, dementia, and other diseases. Scientific evidence about chronic illness and toxic chemicals is withheld from the public through stunningly elaborate efforts so that business can continue as usual"--